Enucleation of Bulbus Oculi in Domestic Cats Patients with Orbital Tumors - Ramadhan, Juliadi; Nafis S, Muhammad; Ridho Gelagar, Ario; Aulia, Usma; Zukiaturrahmah, Anna; Sukmawati, Yofa (Future Science, 2023)
The eye is an essential organ for living things, as one of the five senses of the eye is very vulnerable to infectious or non-infectious diseases. The orbital tumor is one of the disorders in the cat's eye that can attack the eye muscles, nerves, and lacrimal glands. This study aims to diagnose and treat the enucleation of bulbus oculi in domestic cats and patients with orbital tumors. This activity was carried out at the Veterinary Practice